EFEKTIVITAS KONSELING KELOMPOK DENGAN TEKNIK EXPRESSIVE WRITING UNTUK MENINGKATKAN KEMAMPUAN PENGENDALIAN EMOSI SISWA SMP - Putri, Firly Septiana; Yessy Elita; Adif Jawadi Saputra (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2025)
Emotional regulation is a crucial skill for students in dealing with academic and social pressures. However, many students still struggle to manage their emotions effectively. This study aims to examine the effectiveness of group counseling using the expressive writing technique in improving emotional regulation among junior high school students. The research employed a quantitative method with a pretest-posttest control group design. The sample consisted of 10 students divided into two groups: experimental and control. The experimental group received group counseling with the expressive writing technique, while the control group participated in group counseling without the technique. Data were collected using an emotional regulation scale administered before and after the intervention and analyzed using an Independent Sample T-test. The results showed a significant improvement in emotional regulation in the experimental group compared to the control group (p < 0.05). These findings indicate that group counseling with expressive writing is an effective strategy to help students manage their emotions. Therefore, this technique can be recommended as an alternative intervention for school counselors to enhance students’ emotional well-being. Keywords: Group Counseling, expressive writing, emotion regulation, students